Intertwined -isms: an exploration of relationships between ageism and sexism in workplace and non-work contexts - Bae, Sangkyung; Choi, Moon (Frontiers in Psychology, 2023)
This study aimed to examine the association of workplace-based ageism with (a) ageism in non-work contexts and (b) workplace-based sexism. Data came from an online survey of workers in South Korea, with a sample stratified by gender and age group (N = 600; mean age = 43.6 years, range 20–74). Workplace-based ageism was measured using the Workplace Intergenerational Climate Scale (WICS). Other measures included the Fraboni Ageism Scale (FAS) and the Workplace Sexism Culture Scale (WSCS). A series of logistic regression models for endorsing the most workplace ageism (i.e., scoring in WICS bottom quartile) were estimated. Results showed that with each unit increase in FAS scores, the probability of belonging to the WICS bottom quartile increased by 7% while controlling for sociodemographic characteristics [odds ratio (OR) = 1.07, 95% confidence interval (CI) = 1.04–1.10, p < 0.01]. Likewise, when WSCS scores increased by one unit, the probability of belonging to the WICS bottom quartile increased by 8% while controlling for sociodemographic characteristics (OR = 1.08, 95% CI = 1.04–1.12, p < 0.01). Findings suggest that ageism and sexism may be intertwined across workplace and non-work contexts.